Perlindungan Hukum Terhadap Korban Perdagangan Perempuan Dan Anak (Trafficking) (Studi Pengadilan Negeri Medan) - Lisana Dewi Sidqin Tekualu; Anggreini Atmei Lubis; Riswan Munthe (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Human trafficking is a special criminal act that has been going on for a long time and is very difficult to eradicate. Medan City is one of the biggest cities in Indonesia which is one of the cities contributing to the exploitation of women and children, due to population growth that is far more dominant by women compared to men. This type of research is a normative juridical descriptive nature. Forms of legal protection for victims of trafficking of women and children are direct and indirect. It can directly be in the form of compensation in the form of restitution and compensation, and providing protection in the rights of other victims, such as giving a new identity, granting physical and psychological rehabilitation, and so forth. Indirect protection is the pouring of rules regarding trafficking for potential victims with the threat of criminal confinement and fines. In upholding the law to traffickers, it can be carried out in several stages, namely investigation and investigation by the police, examination of the completeness of case files by the public prosecutor, examination in trial, and carrying out a decision (execution) from the court